A159 ARE MOBILE HEALTH TECHNOLOGIES SUPPORTING COLONOSCOPY PREPARATION ASSOCIATED WITH BETTER PATIENT OUTCOMES: A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS. (26th February 2020) - El Sheikh, M; Lee, G; El Bizri, M; Sewitch, M J
Abstract: Background: Mobile health technologies are innovative solutions for delivering instructions to patients preparing for their colonoscopy appointments. Aims: To systematically review the literature of the effect of smartphone-based technologies supporting colonoscopy appointment preparation on patient outcomes. Methods: With the assistance of a librarian, one author searched MEDLINE, EMBASE, CINAHL and CENTRAL for randomized controlled trials (RCTs) that evaluated the effect of smartphone-based technologies for colonoscopy preparation on bowel cleanliness and user satisfaction. Two independent reviewers extracted data on patient and intervention characteristics and study outcomes, and appraised study quality using the Cochrane Risk-of-Bias tool. Summary statistics were generated using random effects models for the trials that used either the Boston Bowel Preparation Scale (BPPS) or the Ottawa Bowel Preparation Scale (OBPS). Statistical heterogeneity was assessed using I 2 . Results: Ten RCTs met our inclusion criteria. Smartphone-based interventions included apps, SMS text messages, video clips, camera apps, and social media apps. Most studies showed smartphone-based interventions were associated with better quality bowel cleanliness scores and higher user satisfaction compared to usual care. Standardized mean differences for the BBPS and OBPS differed between the intervention and control groups [SMD 0.57, 95%CI 0.18, 0.95] and [SMD -0.39, 95%CI -0.59, -0.19], respectively. Statistically significant statistical heterogeneity was found for the meta-analyses for the trials employing the BBPS (I 2 =80%, p=0.03) but not for the trials using the OBPS (I 2 =45%, p=0.16). All RCTs were at high risk of bias from non-blinded participants, and most studies were at high or unclear risk of bias due to lack of allocation concealment. Funnel plots to evaluate publication bias were not generated as there were too few studies with sufficient data to analyze. Conclusions: This systematic review found that smartphone-based technology users had better bowel cleanliness quality scores and higher satisfaction with the method of delivering instructions compared to patients given usual care. Given that all RCTs were at high risk of bias, high-quality RCTs that blind participants and conceal study group allocation are needed. Funding Agencies: CIHRDepartment of Medicine, McGill University and the Research Institute of the McGill University Health Centre